Urban Connectors: Blue, Green and Grey as Catalysts for City Liveability in the Built Environment - Zulkarnain, Mustapha Kamal; Bilyamin, Siti Fatimah Ilani (MAJ - Malaysia Architectural Journal, 2025)
In urban development, urban connectors, encompassing blue (water-based) and green (nature-based) elements as well as grey connectors enhance city liveability. This paper explores their significance for professionals in the built environment. Blue connectors, like rivers and waterfronts, offer benefits such as attractive community spaces, active transportation promotion, and sustainable storm water management. Real-world cases inspire replication. Green connectors, such as parks and urban forests, improve aesthetics, well-being, and air quality. Case studies emphasize the need for preservation and expansion. Blue and green connectors foster city connectivity. Multimodal networks reduce traffic congestion, promote walkable neighbourhoods, and healthier lifestyles. Realizing urban connectors' potential demands interdisciplinary collaboration. Architects, planners, policymakers, and stakeholders must integrate these elements into urban design for vibrant, sustainable cities. In summary, urban connectors, both blue and green, enhance city liveability. This paper encourages built environment professionals to embrace them, creating cities that harmonize with nature and enhance residents' quality of life.